Long-term influence of high alkalinity on the performance of photosynthetic biogas upgrading. (1st December 2020) - Rodero, María del Rosario; Severi, Cristian Alfredo; Rocher-Rivas, Ricardo; Quijano, Guillermo; Muñoz, Raúl
Graphical abstract: Highlights: Higher alkalinity resulted in a higher efficiency and robustness of CO2 removal. Photosynthetic activity decreased at a high alkalinity in the cultivation broth. CO2 stripping increased at higher alkalinity despite the high pH in pond. The increase in biomass concentration exerted a negative impact on CO2 removal. No biomass harvesting ultimately mediated a decrease in photosynthetic activity. Abstract: The alkalinity of the cultivation medium plays a key role on photosynthetic biogas upgrading, exerting impact not only on the mass-transfer of CO2 and H2 S in the biogas scrubbing column but also on the subsequent CO2 uptake or stripping to the atmosphere. The long-term performance of algal-bacterial processes devoted to the concomitant removal of CO2 and H2 S from biogas in a 180 L open pond interconnected to a 2.5 L biogas scrubbing column via an external liquid recirculation of supernatant from a 8 L conical settler under process operation at high inorganic carbon (IC) concentrations was assessed. The influence of biomass concentration in the cultivation medium on process performance was also evaluated. CO2 concentrations in the upgraded biogas fluctuated between 1.5 and 4.4% at IC concentrations in the cultivation medium of 1200 mg C L −1, and remained almost constant (0.7 ± 0.1%) at IC concentrations > 2400 mg C L −1 . However, the increase in the IC concentration from 1203 to 3476 mg C L −1 entailed an increase in C-CO2 stripping from 14.5 to 33.4% of the IC input to the system. The increase in biomass concentration from 0.33 to 1.38 g SSV L −1 entailed a reduction in CO2 removal of 1.1% even under process operation at high alkalinity. H2 S removal efficiencies of 100% were achieved regardless the IC or biomass concentration.